Intelligence Émotionnelle Artificielle: Applications en Psychologie et Perspectives Futures - Brir, Hicham (Darul Yasin Al Sys, 2025)
This article examines the emergence of Artificial Emotional Intelligence (AEI) in psychology, an interdisciplinary field integrating deep learning, natural language processing, and affective computing. It explores its promising applications—such as therapeutic chatbots and predictive diagnostic tools—to democratize access to mental healthcare and personalize interventions. Major challenges, including interpreting cultural nuances, managing algorithmic biases, safeguarding sensitive data, and limitations in replicating human empathy, are critically analyzed. The study emphasizes the need for transdisciplinary collaboration (psychology, engineering, ethics) to guide its deployment, validate clinical efficacy, and preserve the integrity of therapeutic practices. Finally, AEI is framed as a technological adjunct to traditional methods, enhancing—without replacing—human interactions central to psychological care.